PCR-based identification of Klebsiella pneumoniae subsp. rhinoscleromatis, the agent of rhinoscleroma. - Cindy Fevre; Virginie Passet; Alexis Deletoile; Valérie Barbe; Lionel Frangeul; Ana S Almeida; Philippe Sansonetti; Régis Tournebize; Sylvain Brisse (Public Library of Science (PLoS), 2011)
Rhinoscleroma is a chronic granulomatous infection of the upper airways caused by the bacterium Klebsiella pneumoniae subsp. rhinoscleromatis. The disease is endemic in tropical and subtropical areas, but its diagnosis remains difficult. As a consequence, and despite available antibiotherapy, some patients evolve advanced stages that can lead to disfiguration, severe respiratory impairment and death by anoxia. Because identification of the etiologic agent is crucial for the definitive diagnosis of the disease, the aim of this study was to develop two simple PCR assays. We took advantage of the fact that all Klebsiella pneumoniae subsp. rhinoscleromatis isolates are (i) of capsular serotype K3; and (ii) belong to a single clone with diagnostic single nucleotide polymorphisms (SNP). The complete sequence of the genomic region comprising the capsular polysaccharide synthesis (cps) gene cluster was determined. Putative functions of the 21 genes identified were consistent with the structure of the K3 antigen. The K3-specific sequence of gene Kr11509 (wzy) was exploited to set up a PCR test, which was positive for 40 K3 strains but negative when assayed on the 76 other Klebsiella capsular types. Further, to discriminate Klebsiella pneumoniae subsp. rhinoscleromatis from other K3 Klebsiella strains, a specific PCR assay was developed based on diagnostic SNPs in the phosphate porin gene phoE. This work provides rapid and simple molecular tools to confirm the diagnostic of rhinoscleroma, which should improve patient care as well as knowledge on the prevalence and epidemiology of rhinoscleroma.